Consenting to servitude : a case study of restaurant workers in Gauteng. - Loonat, Atiyyah (My University, 2013)
Due to high levels of globalization and outsourcing of employment an important aspect emerges which is the concept of decent work. This concept is important in that the struggle for many companies to stay afloat under global competition requires the cutting of costs. The cost which is the most easy to manipulate is that of labour. Through global competitiveness companies often increase working hours, decrease wages and decrease benefits for employees. This has caused increased attention to the idea and concept of decent work. This leads to the problem of providing and assuring decent work on a global scale. Decent work is an objective of the International Labour Organization (ILO) which aims to provide equitable employment to people of all spheres. This goal is wide and deals with nine indicators which are quantitative in nature. However these aspects do not deal with the subjective measures which pertain to employment. These subjective measures are as important as the quantitative measures. To better attain the goal of decent work this report argues that there is a need for the incorporation of these subjective measures when determining the level of decent employment. For the purposes of this research report the subjective measures are collectively termed job satisfaction. However while this combination of objective and subjective indicators better reflects working conditions, there is a need for more comprehensive concepts in understanding vulnerable work. In order to develop this deeper understanding of vulnerable work. This research report utilizes various literature in in the sociology of work . The restaurant industry in Gauteng is used as the site for this research report as a means of illustrating the pitfalls to the narrowly defined concepts of decent work and job satisfaction. This industry is particularly interesting as it is very different from other sectors as it is marked by interactive service work that involves high levels of emotional labour. Tips play a large role in supplementing the workers income. Tips , the report argues, is a means of workers consenting to servitude as they actively participate in their exploitation through conforming to the enterprises interests. This is not merely done through the system of tipping but also through their performance of emotional labour which is often increased in order to play these “games “which allow for higher tips. Consenting to servitude is not only the acceptance of exploitation but also the creation of a submissive and subservient work force. The notion of consenting to servitude is what lacks in both concepts. Exploitation plays a large role in whether a job is deemed decent or not but it is largely ignored within both the concepts of decent work and job satisfaction. Instead it is necessary to go beyond these two concepts and draw on the body of social theory on the world of work such as Burawoy and Foucault, if one wants to explain the nature of work and workers responses in the hospitality industry in Gauteng. This illustrates that every workplace is different and requires differing sets of indicators. The concepts of job satisfaction and decent work although incomplete on their own carry various advantages and cannot merely be dismissed.
Keywords: Restaurants--South Africa--Employees.; Job satisfaction--South Africa.; Work--Psychological aspects.